Research progress of Traditional Chinese Medicine nursing for chest stuffiness and pain syndrome (胸痹心痛病中医护理的研究进展) - LI Jinghuan (李靖嬛); YUE Lina (岳丽娜) (中西医结合护理)
Coronary heart disease, angina, myocardial infarction are placed under the category of chest stuffiness and pain syndrome in Traditional Chinese Medicine(TCM). The incidence of chest pain and heartache disease has being increasing year by year, which has seriously harmed human physical and mental health. TCM nursing takes holistic nursing as the core, and determines the nursing principles under the guidance of syndrome differentiation, so as to implement targeted TCM nursing for patients, and play its due role in the prevention and treatment of chest stuffiness and pain syndrome. This paper analyzed the current situation of TCM nursing application, summarizes the existing problems, analyzes the future research progress, and provided reference for the improvement of TCM nursing quality. (现代医学中的冠状动脉粥样硬化性心脏病、心绞痛、心肌梗死等属中医“胸痹心痛”范畴。胸痹心痛病发病率呈逐年上升趋势, 已经严重危害人类的身心健康。中医护理以整体性护理为核心, 在辨证指导下确定护理原则, 针对性对患者实施中医护理, 在防治胸痹心痛病方面发挥了重要作用。本文从胸痹心痛病的中医护理应用现状进行分析, 总结目前存在的问题, 分析相关措施, 旨在为保持和发挥中医护理特色优势, 提高胸痹心痛病中医护理效果和工作质量提供参考。)